Clinical, Endoscopic and Histological Outcomes in Induction of Moderate-to-Severe Ulcerative Colitis: A Systematic Review with Meta-Analysis. (8th September 2020) - Magro, Fernando; Estevinho, Maria Manuela; Dias, Cláudia Camila; Correia, Luís; Lago, Paula; Ministro, Paula; Portela, Francisco; Feakins, Roger; Danese, Silvio; Peyrin-Biroulet, Laurent
Abstract: Background and Aims: Interest in histology for ulcerative colitis [UC] has increased recently. This systematic review and meta-analysis aims to assess, for the first time, whether histological outcomes are more informative than endoscopic and clinical outcomes in distinguishing the impact of intervention over placebo in induction trials. Methods: MEDLINE, ScienceDirect and Cochrane Central Register of Controlled Trials were searched to identify randomized placebo-controlled trials [RCTs] enrolling moderate-to-severe UC patients. Studies were assessed using the Quality Assessment Tool for Studies with Diverse Designs. We analysed the pooled proportion of patients achieving clinical, endoscopic and histological remission and response after a pharmacological intervention and compared the results with those of placebo-treated patients by using a random-effects model. Results: From 889 identified records, 13 RCTs were included. The odds ratio [OR] for remission was higher in patients receiving intervention than in those under placebo for clinical (OR 2.13, 95% confidence interval [CI] 1.33–3.43), endoscopic [OR 1.46, 95% CI 0.19–11.18] and histological remission [OR 1.85, 95% CI 1.20–2.84]. Significant differences were observed for all response outcomes [clinical: OR 2.27, 95% CI 1.84–2.85; endoscopic: OR 2.16, 95% CI 1.51–3.10; histological: OR 3.63, 95% CI, 1.41–9.36]. No significant heterogeneity existed; no subgroup effects were found for duration of the induction or histological scale [ p  > 0.05]. Clinical and histological remission and endoscopic response were concordant in discriminating interventions from placebo. Conclusion: Histological outcomes are informative in trials of moderate-to-severe UC. Further studies analysing histology at the end of induction are needed to confirm its relevance in distinguishing the efficacy of an intervention over placebo in comparison to clinical and endoscopic outcomes and to explore its prognostic value.